2021
DOI: 10.3390/app11073293
|View full text |Cite
|
Sign up to set email alerts
|

L-Citrulline: A Non-Essential Amino Acid with Important Roles in Human Health

Abstract: L-Arginine (Arg) has been widely used due to its functional properties as a substrate for nitric oxide (NO) generation. However, L-citrulline (CIT), whose main natural source is watermelon, is a non-essential amino acid but which has important health potential. This review provides a comprehensive approach to different studies of the endogenous synthesis of CIT, metabolism, pharmacokinetics, and pharmacodynamics as well as its ergogenic effect in exercise performance. The novel aspect of this paper focuses on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 143 publications
0
37
0
1
Order By: Relevance
“…The role of citrulline in the regulation of immune function is increasingly being recognized. Citrulline is a nutritionally non-essential amino acid which plays an important role in arginine biosynthesis, the nitric oxide cycle, and the urea cycle ( 32 ). The metabolism of citrulline is unique in that it is not used by the intestine or taken up by the liver and, thus, bypasses splanchnic extraction ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…The role of citrulline in the regulation of immune function is increasingly being recognized. Citrulline is a nutritionally non-essential amino acid which plays an important role in arginine biosynthesis, the nitric oxide cycle, and the urea cycle ( 32 ). The metabolism of citrulline is unique in that it is not used by the intestine or taken up by the liver and, thus, bypasses splanchnic extraction ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Magnusson M. et al reported that higher levels of L-citrulline in subjects with no CVD at baseline were associated with cardiovascular risk during 12 years of follow-up; L-citrulline was also cross-sectionally related to CAS [ 63 ]. It was shown that the disturbances of the L-arginine-NO-L-citrulline pathway in diabetes and metabolic syndrome are closely related to inflammation and oxidative stress [ 64 ]—the hallmarks of diabetic vascular complications [ 36 ]. At the same time, it was demonstrated that L-citrulline supplementation increases NO levels [ 65 ], improves insulin resistance, and decreases HbA1c and concentrations of inflammatory markers in patients with T2D [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…L-citrulline is used to prevent endothelial dysfunction in cardiovascular diseases and diabetes, and treat erectile dysfunction. In addition, due to its role in arginine metabolism, L-citrulline is a potential agent for treating cancer [ 11 ].…”
Section: Introductionmentioning
confidence: 99%